Genetic diversity of Anaplasma marginale in cattle and in putative novel Anaplasma species from wildlife in Mpumalanga, South Africa - Collins, Nicola E. (University of Pretoria, 2024)
Thesis (PhD (Veterinary Tropical Diseases))--University of Pretoria, 2024.